Environmental cues during overland dispersal by three freshwater invaders: Eriocheir sinensis, Pacifastacus leniusculus, and Procambarus clarkii (Crustacea, Decapoda) - Marques, M. (2015)
Freshwater crustaceans are known to disperse overland, aiding the invasion of new environments. To analyze the effect of environmental variables (humidity, temperature, illuminance, vegetation, and slope) on the movement direction of Eriocheir sinensis (H. Milne Edwards, 1853), Pacifastacus leniusculus (Dana, 1852) and Procambarus clarkii (Girard, 1852) in land, the animals were placed at the centre of a metal gutter and given a choice between two values of each variable. Chi-squared tests revealed significant preferences for E. sinensis to move downhill, P. leniusculus to move toward cooler areas and P. clarkii to move downhill and toward cooler areas. To test the ability of P. leniusculus and P. clarkii (E. sinensis was not present at the testing site) to return to water, they were placed in a circular arena near the river bank and their direction of movement was recorded. Chi-squared tests revealed that P. leniusculus, when isolated and in groups of 6, showed a significant tendency to move downstream, but not directly toward the water. P. clarkii showed no significant preference in movement direction. Since movement direction and overland dispersal are influenced by environmental gradients of temperature and elevation, these variables are fundamental for predicting autonomous overland dispersal and colonization patterns.